Tropes As A Means Of Artistic Expressiveness In The Idiolect Of M.Bulgakov - Sidorkova Luiza Ravshanovna; Bahronova Noilya Khasan Kizi (Peerian Journals Publishing, 2025)
The article examines the system of tropes as one of the essential components of the artistic-expressive means of the Russian language, which are characteristic of M. Bulgakov’s idiolect
Keywords: trope; metaphor; metonymy